Assessment of readiness of academic emergency departments in the central region of Saudi Arabia to receive a sick child - Alhajjaj, Fahad Saleh; Aldamigh, Abdullah Saleh (International Journal of Health Sciences, 2017)
Objective: We sought to assess the readiness of general emergency departments (EDs) in academic hospitals in the central region of the Kingdom of Saudi Arabia (KSA) to manage pediatric patients using an international tool: The American Academy of Pediatrics, American College of Emergency Physicians, and Emergency Nurses Association guidelines, which include facilities, personnel, safety, and other components. Methods: We assessed eligible centers during multiple visits from January 2016 to May 2016 in which we inspected the EDs and conducted interviews with their respective leadership in which we independently recorded our observations. We meet afterward to reach a consensus. Four centers were eligible for enrollment out of eight. Results: 437,548 patient visits were recorded in 2015 in four academic EDs served by 176 beds. 193 parameters as well as basic demographic data were evaluated. The average travel time from an academic ED to an affiliated pediatric ED was 4.2 min (standard deviation: 1.25). Only two centers had a dedicated pediatric resuscitation bed and none had a separate pediatric crash cart. Overall performance for all centers was 53% in all test parameters. Average scores were 75% for administration and staffing and 49.6% for equipment and medications. None of the centers had a weighing scale or a hypothermia monitor, and all centers neither had policies for family-centered care nor care of children during disasters. Conclusion: Evaluation of academic EDs in the central region of the KSA using an international tool revealed low overall scores with critical components needed for pediatric emergency care missing.